Usefulness of intraoperative endoscopy in pediatric surgery: state of the art - Borgogni, Rachele; Gaiani, Federica; Di Mario, Francesco; Fornaroli, Fabiola; Leandro, Gioacchino; Bizzarri, Barbara; Ghiselli, Alessia; de' Angelis, Gian Luigi; Casolari, Emilio (Acta Biomedica Atenei Parmensis, 2018)
Introduction: Intraoperative endoscopy is a procedure that supports open and laparoscopic surgery, helping the surgeon to identify the presence of endoluminal gastrointestinal lesions which need to be treated, with a correct diagnosis and an adequate therapy. Material and methods: A search on PubMed was performed using “intraoperative esophagoscopy”, “intraoperative duodenoscopy”, and “intraoperative enteroscopy” as Mesh terms. The applied exclusion criteria were: papers written before 2000, not concerning pediatric or gastrointestinal pathology, literature-review articles, language different from English. Results: Sixteen studies from 2000 to 2018 were included. Overall, 1210 patients were treated. Different pathologies were considered. Complications were observed in a range of 0.3-14%. The most frequent complications were perforation, bleeding and mucosal tear. Mortality ranged between 0.7% and 1,2%. Conclusion: Intraoperative endoscopy is an indispensable tool for gastrointestinal surgery. In the hands of experienced endoscopists, intraoperative endoscopy can be performed safely, in time-efficient manner, facilitating diagnosis and treatment.